2020
DOI: 10.2147/copd.s267114
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characteristics of Patients with Chronic Obstructive Pulmonary Disease Exposed to Different Environmental Risk Factors: A Large Cross-Sectional Study</p>

Abstract: Purpose: Tobacco smoking, biomass smoke, and occupational exposure are the main risk factors for chronic obstructive pulmonary disease (COPD). The present study analyzes data on exposure to these factors in a cohort of patients with COPD and assesses their differences in demographic and clinical characteristics. Patients and Methods: The cross-sectional observational study was conducted from November 2016 to December 2019. Inclusion criteria were patients aged over 40 years old with post-bronchodilator forced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
16
1
1
Order By: Relevance
“…COPD patients suffered from occupational exposure developed more severe dyspnea than those exposed to tobacco alone. 6 However, non-adherence to therapy can be surprising high in our study, that in very symptomatic patients (mMRC grade ≥ 2) and less symptomatic patients (mMRC grade < 2), the future non-adherence rate was as high as 48.61% (70/144) and 75.36% (52/69), respectively. Disease heterogeneity for pneumoconiosis with COPD and subjective cognition on COPD may play a role in individual adherence behavior.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…COPD patients suffered from occupational exposure developed more severe dyspnea than those exposed to tobacco alone. 6 However, non-adherence to therapy can be surprising high in our study, that in very symptomatic patients (mMRC grade ≥ 2) and less symptomatic patients (mMRC grade < 2), the future non-adherence rate was as high as 48.61% (70/144) and 75.36% (52/69), respectively. Disease heterogeneity for pneumoconiosis with COPD and subjective cognition on COPD may play a role in individual adherence behavior.…”
Section: Discussioncontrasting
confidence: 53%
“…Notably, our group first reported that patients with COPD who suffered from occupational exposure developed more severe dyspnea than those exposed to tobacco alone. 6 Moreover, COPD patients exposed to occupational dust have distinct exposure pattern and different imaging and pathology features compared to those exposed to cigarette smoke. 2 , 7 , 8 The effect of dust on emphysema is small 7 but on opacity profusion and fibrosis 8 is prominent when compared to the effect of tobacco smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure was defined as exposure to dust, gases, chemical substances, paints, or metals at work for at least 8 hours per day for at least 1 year. 15 …”
Section: Methodsmentioning
confidence: 99%
“…With the progression of COPD, the burden of symptoms increases and quality of life declines. Symptomatic patients with COPD (group B and D) account for the vast majority in China ( Duan et al, 2020 ). Furthermore, compared with patients with well-controlled symptoms, more symptomatic patients have a higher risk of acute exacerbations and poorer disease prognosis ( Roche et al, 2013 ; Miravitlles and Ribera, 2017 ).…”
Section: Introductionmentioning
confidence: 99%